1984
DOI: 10.1111/j.2044-8260.1984.tb00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and identification of facial stimuli by schizophrenics and patients with affective disorders

Abstract: Schizophrenics have been shown to manifest a significant deficit in identifying facial expressions of emotion. The present study sought to determine whether this deficit lay at the level of decoding facial cues of emotion, or whether it is specific to the process of labelling emotional faces. The latter specific deficit would be consistent with the hypothesis of left-hemisphere dysfunction in schizophrenia. Samples of schizophrenics, patients with affective disorders and normal controls were tested on a batter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(114 citation statements)
references
References 0 publications
6
103
1
Order By: Relevance
“…Although, as noted in the introduction, studies comparing the performance of schizophrenia patients on facial emotion processing tasks to other aspects of face processing have produced mixed findings (Novic et al 1984 ;Walker et al 1984 ;Archer et al 1992 ;Kerr & Neale, 1993 ;Laws et al 1996 ;Salem et al 1996), two recent studies have reported greater impairment on facial emotion tasks than on structural encoding of the facial percept (Kucharska-Pietura et al 2005) and on judging age from faces (Schneider et al 2006). Kucharska-Pietura et al (2005) found that 100 patients with schizophrenia (50 chronically ill and 50 in the early stages of illness) showed impairment on both an emotional face processing task and the BFRT.…”
Section: Discussionmentioning
confidence: 99%
“…Although, as noted in the introduction, studies comparing the performance of schizophrenia patients on facial emotion processing tasks to other aspects of face processing have produced mixed findings (Novic et al 1984 ;Walker et al 1984 ;Archer et al 1992 ;Kerr & Neale, 1993 ;Laws et al 1996 ;Salem et al 1996), two recent studies have reported greater impairment on facial emotion tasks than on structural encoding of the facial percept (Kucharska-Pietura et al 2005) and on judging age from faces (Schneider et al 2006). Kucharska-Pietura et al (2005) found that 100 patients with schizophrenia (50 chronically ill and 50 in the early stages of illness) showed impairment on both an emotional face processing task and the BFRT.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to recognize facial expressions of emotions has also been investigated among children, adolescents, and adults with other exceptionalities (Walker, McGuire, & Bettes, 1984;Zabel, 1979). Zabel (1979) Zabel (1979) found the students with special needs to be less accurate overall at recognizing facial expressions of emotion.…”
Section: Emotion and Leaming Disabilities 42mentioning
confidence: 99%
“…Most of these investigations have found that schizophrenia patients have defi-cits in both facial and vocal affect recognition (e.g. Archer et al, 1994;Baudouin et al, 2002;Borod et al, 1993;Edwards et al, 2001;Feinberg et al, 1986;Heimberg et al, 1992;Mandal et al, 1998;Penn et al, 2000;Schneider et al, 1995;Walker et al, 1984), and that these deficits are not related to age, gender, medication status or neuroleptic dose (Kline et al, 1992;Poole et al, 2000;Salem et al, 1996;Schneider et al, 1995).…”
Section: Introductionmentioning
confidence: 99%